Endonuclease Restriction-Mediated Real-Time Polymerase Chain Reaction: A Novel Technique for Rapid, Sensitive and Quantitative Detection of Nucleic-Acid Sequence - Wang, Yi; Wang, Yan; Zhang, Lu; Li, Machao; Luo, Lijuan; Liu, Dongxin; Li, Hua; Cao, Xiaolong; Hu, Shoukui; Jin, Dong; Xu, Jianguo; Ye, Changyun (Frontiers in Microbiology, 2016)
The article reported a novel methodology for real-time PCR analysis of nucleic acids, termed endonuclease restriction-mediated real-time polymerase chain reaction (ET-PCR). Just like PCR, ET-PCR only required one pair of primers. A short sequence (Ss), which was recognized by restriction enzyme BstUI, was attached to the 5’ end of the forward (F) or reverse (R) PCR primer, and the new F or R primer was named EF or ER. EF/ER was labeled at the 5’ end with a reporter dye and in the middle with a quenching dye. BstUI cleaves the newly synthesized double-stranded terminal sequences (5’ end recognition sequences and their complementary sequences) during the extension phase, which separates the reporter molecule from the quenching dye, leading to a gain of fluorescence signal. This process is repeated in each amplification cycle and unaffected the exponential synthesis of the PCR amplification. ET-PCR allowed real-time analysis of single or multiple targets in a single vessel, and provided the reproducible quantitation of nucleic acids. positive results were generated in a relatively short period. The analytical sensitivity and specificity of ETR-PCR were successfully evaluated, detecting down to 250 fg of genomic DNA per tube of target pathogen DNA examined, and the positive results were generated in a relatively short period. Moreover, the practical application of ET-PCR for simultaneous detection of multiple target pathogens was also demonstrated in artificially contaminated blood samples. In conclusion, due to the technique’s simplicity of design, reproducible data and low contamination risk, ET-PCR assay is an appealing alternative to conventional approaches currently used for real-time nucleic acid analysis.